2021
DOI: 10.3390/ijerph18083913
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Excess Mortality and Years of Life Lost to COVID-19 in Norway and Sweden between March and November 2020

Abstract: We estimate the weekly excess all-cause mortality in Norway and Sweden, the years of life lost (YLL) attributed to COVID-19 in Sweden, and the significance of mortality displacement. We computed the expected mortality by taking into account the declining trend and the seasonality in mortality in the two countries over the past 20 years. From the excess mortality in Sweden in 2019/20, we estimated the YLL attributed to COVID-19 using the life expectancy in different age groups. We adjusted this estimate for pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…A similar study in England and Wales showed that YLL increased by 15% during the COVID-19 pandemic and 1350.4 years/100,000 population/year YLL was reported due to COVID-19 ( 46 ). Similar YLLs due to COVID-19 were also reported in studies in the United States (1631.2 years/100.000 populations/year), Spain (664.6 years/100,000 populations/year), Italy (656.0 years/100,000 populations/year), Sweden (413.4 years/100,000 populations/year) during the COVID-19 pandemic ( 45 , 47 , 48 ). The excess in YLL is due to the direct and indirect impact of COVID-19.…”
Section: Discussionsupporting
confidence: 83%
“…A similar study in England and Wales showed that YLL increased by 15% during the COVID-19 pandemic and 1350.4 years/100,000 population/year YLL was reported due to COVID-19 ( 46 ). Similar YLLs due to COVID-19 were also reported in studies in the United States (1631.2 years/100.000 populations/year), Spain (664.6 years/100,000 populations/year), Italy (656.0 years/100,000 populations/year), Sweden (413.4 years/100,000 populations/year) during the COVID-19 pandemic ( 45 , 47 , 48 ). The excess in YLL is due to the direct and indirect impact of COVID-19.…”
Section: Discussionsupporting
confidence: 83%
“…The increase or decrease in mortality from one epiyear to the next, however, is only weakly related to how low or high mortality is in the epiyear. Rypdal et al [ 12 ] studied this.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to virus-preventing strategies, several researchers have reported that Sweden has differed from a large number of other settings, most importantly due to the absence of full stay-at-home orders or lockdown closures in Sweden ( Baral et al, 2020 ; Farina and Lavazza, 2020 ; Yarmol-Matusiak et al, 2021 ). A large difference in fatal COVID-19 cases has been seen between Sweden and neighbor Nordic countries with lower death rates ( Rypdal et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%